Strategy-switching dynamics with applications - Li, Yuting (2011)
Dynamic theory has recently been applied to study the distribution patterns of the profit driven competing mechanism in games with multiple strategies (Huang, 2010). Though this kind of game appears more and more frequently in real markets, the model is not mature enough. The current study is dedicated to make the model more complete and realistic by including situations of all members moving according to their own will, collusion and cheating on the basis of previous framework.